MorphoLex: A derivational morphological database for 70,000 English words - Sánchez-Gutiérrez, Claudia H.; Mailhot, Hugo; Deacon, S. Hélène; Wilson, Maximiliano A. (Behavior research methods, 2018)
Most of the new words a reader will find are morphologically complex. Also, theoretical models of language processing propose that morphology plays an important role in visual word processing. Nevertheless, studies on the subject show contradicting results that are difficult to reconcile. One factor that may explain this is the lack of a sizeable and reliable morphological database. As a consequence, there are enormous methodological differences in the way the values for morphological variables are calculated across studies. We present a sizeable and freely available database with six new variables for affixes and three for roots for 68,624 words from the English Lexicon Project. We further studied by means of regression models the influence of these new variables on the lexical decision latencies of 4,724 morphologically complex nouns that included one root and one suffix. Results showed that root frequency and suffix length had a facilitatory effect, whereas the percentage of more frequent words in the morphological family of the suffix had an inhibitory effect on latencies. After controlling for collinearity, root family size, suffix family size, suffix P*, and suffix frequency also had facilitatory effects. These results shed new light on the importance of suffix length and the frequency of the lexical competitors of the family of a suffix. This database represents a valuable resource for studies on the effect of morphology in visual word processing in English and can be found at https://github.com/hugomailhot/MorphoLex-en .